Evaluation of a Paediatric Trauma Social Worker Service. Issue 4 (1st October 2020) - Curtis, Kate; Van, Connie; Foster, Kim; Winters, Jacqueline; Mitchell, Rebecca
ABSTRACT: Injury is the leading cause of hospitalisation of children in Australia and can cause ongoing physical and psychological morbidity. Hospital staff provide excellent physical care to injured children, but there is a need for models of care that improve psychosocial care. To address this gap, a trauma support social work service was trialled at an Australian paediatric trauma hospital, to guide families of injured children through the healthcare system from the day of the child's injury to 6 months following discharge. A mixed methods approach was used to evaluate the service and used a range of data sources—trauma registry records, the Trauma Support Coordinator (TSC) journal, staff surveys, and interviews. Findings from this small study suggest the TSC was able to improve the coordination of care, provide information, and meet the emotional needs of families of injured children. Ways to improve the effectiveness and acceptance of the TSC role were also identified. IMPLICATIONS Injured children should be allocated a dedicated TSC for their entire stay in hospital to provide continuity of care for the child and their family. Situating the TSC role in the Emergency Department will allow for early contact with families when support is most crucial. Incorporation of the TSC role into the social work roster will reduce "doubling up" of psychosocial services offered to families.